2014
DOI: 10.1038/nature13393
|View full text |Cite
|
Sign up to set email alerts
|

Targeting transcription regulation in cancer with a covalent CDK7 inhibitor

Abstract: Tumor oncogenes include transcription factors that co-opt the general transcriptional machinery to sustain the oncogenic state 1 , but direct pharmacological inhibition of transcription factors has thus far proven difficult 2 . However, the transcriptional machinery contains various enzymatic co-factors that can be targeted for development of new therapeutic candidates 3 , including cyclin-dependent kinases (CDKs) 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

63
961
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 741 publications
(1,027 citation statements)
references
References 30 publications
63
961
1
2
Order By: Relevance
“…1A). We next tested inhibitors of TFIIH CDK7 kinase activity (THZ) and the P-TEFb CDK9 inhibitor flavopiridol (FP) in our assay (47,48). Both THZ and flavopiridol have been shown previously to block transcription elongation in vitro (48,49).…”
Section: Oga Activity Is Required For Efficient Elongation In Vitro-mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). We next tested inhibitors of TFIIH CDK7 kinase activity (THZ) and the P-TEFb CDK9 inhibitor flavopiridol (FP) in our assay (47,48). Both THZ and flavopiridol have been shown previously to block transcription elongation in vitro (48,49).…”
Section: Oga Activity Is Required For Efficient Elongation In Vitro-mentioning
confidence: 99%
“…The full-length labeled RNA run-off product of 548 nucleotides is indicated by the arrow. THZ is an inhibitor of the CDK7 kinase subunit of TFIIH, and FP is a P-TEFb inhibitor (47,48). PUGNAc and Thiamet G were added after a 30 h PIC formation step as our previous work suggested that OGA might be required for PIC formation (43).…”
Section: Oga Activity Is Required For Efficient Elongation In Vitro-mentioning
confidence: 99%
“…Still, while CDK9 inhibition broadens the possibilities for ''anti-MYC'' therapy, its impact is not as great as MYC inhibition. Perhaps combinatorial therapies using the multikinase inhibitor sorafenib, a recently developed covalent CDK7 inhibitor that targets transcription regulation (Kwiatkowski et al 2014), or those targeting other MYC activities will synergize with CDK9 inhibition in producing strong anti-tumor effects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed flavopiridol, a broad-acting kinase inhibitor that potently inhibits both CDK7 and CDK9 activity, has shown some promise in the treatment of several types of hematologic malignancies [15]. Recently, a drug prototype that is a remarkably selective inhibitor of CDK7 has been described [16]. This compound, THZ1, achieves relative selectivity for CDK7 through a covalent binding mechanism mediated by a reactive cysteine residue located outside the kinase pocket.…”
Section: Targeting Transcription Kinasesmentioning
confidence: 99%